“Outside-to-inside,” “inside-to-outside,” and “intrinsic” endogenous pathogenic mechanisms in atopic dermatitis: keratinocytes as the key functional cells involved in both permeability barrier dysfunction and immunological alterations - Hatano, Yutaka; Elias, Peter M. (Frontiers in Immunology, 2023)
Permeability barrier disruption has been shown to induce immunological alterations (i.e., an "outside-to-inside" pathogenic mechanism). Conversely, several inflammatory and immunological mechanisms reportedly interrupt permeability barrier homeostasis (i.e., an "inside-to-outside" pathogenic mechanism). It is now widely recognized that alterations of even a single molecule in keratinocytes can lead to not only permeability barrier dysfunction but also to immunological alterations. Such a simultaneous, bidirectional functional change by keratinocytes is herein named an "intrinsic" pathogenic mechanism. Molecules and/or pathways involved in this mechanism could be important not only as factors in disease pathogenesis but also as potential therapeutic targets for inflammatory cutaneous diseases, such as atopic dermatitis, psoriasis, and prurigo nodularis. Elevation of skin surface pH following permeability barrier abrogation comprises one of the key pathogenic phenomena of the "outside-to-inside" mechanism. Not only type 2 cytokines (e.g., IL-4, IL-13, IL-31) but also type 1 (e.g. IFN-γ), and type 3 (e.g., as well as several other inflammatory factors (e.g. histamine) can disrupt permeability barrier homeostasis and are all considered part of the "inside-to-outside" mechanism. Finally, examples of molecules relevant to the "intrinsic" pathogenic mechanism include keratin 1, filaggrin, and peroxisome proliferator-activated receptor-α (PPAR).